Validation of Thrixspermum ravanii (Aeridinae, Orchidaceae), a new species from the Philippines - Sodusta, Patrick Jason A.; Cootes, Jim (Phytotaxa, 2024)
Thrixspermum ravanii was first proposed on 29 November 2012 in a Portable Document Format (PDF) file published by OrchideenJournal (Cootes & Tiong, 2012). The proposed species however, was not effectively published according to the Shenzhen Code (Turland et al., 2018), and is currently treated by the International Plant Names Index (IPNI) as nomen invalidum. Firstly, the journal published the proposed new species in a style that is evidently different from its final and official issue. Specifically, the new species was presented in manuscript form, which deviates from the standard publication format of the journal. Additionally, the published form lacked the volume number and pagination, which are characteristic features of the final and official issue. Secondly, the publication used an International Standard Serial Number (ISSN) intended for print material rather than one suited for online media. In Cootes & Tiong (2012), the ISSN indicated is 1864-9459, which according to the ISSN portal is registered for print medium. According to the Art. 30.2 of the Shenzhen Code (Turland et al., 2018), an electronic publication is not effectively published if there is an indication that it is not the final version. Furthermore, the code explicitly mentioned that an inappropriate ISSN does not result in effective publication under Art. 29.1 (Turland et al., 2018). Thus, the name for the new species was not effectively published because it did not meet the conditions of effective publication. To validate T. ravanii, an English description and diagnosis of the species are presented herein.